Strategies For Determining Sharia Insurance Target Market - tiara Juliana Jaya; Yullina Devvie Sari; Roi Anju Immanuel (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this research is to know the strategy of determining the target market in PRUlink Sharia assurance products pt. Prudential life assurance. The method used in this study is qualitatively descriptive. Descriptive statistical analysis techniques, stages of data analysis techniques Data collection, Data reduction data reduction, Presentation of data Presentation data, Withdrawal of conclusions. Strategy to determine the target market on PRUlink sharia assurance account products at PT. Prudential Life Assurance is: use the six o concept strategy so that the target market type. Types of target market selected, observation to the location, Muslim community, Grouping of insurance policy candidates, Ability factor by looking at a salary range of 2 million, and Prospective insurance policy that is at productive age for those between the ages of 25-40 years.